Mild iron overload in patients carrying the HFE S65C gene mutation: a retrospective study in patients with suspected iron overload and healthy controls. Issue 5 (1st November 2002) - Holmström, P; Marmur, J; Eggertsen, G; Gåfvels, M; Stål, P
Abstract : Background and aims: The role of the HFE S65C mutation in the development of hepatic iron overload is unknown. The aim of the present study was: (A) to determine the HFE S65C frequency in a Northern European population; and (B) to evaluate whether the presence of the HFE S65C mutation would result in a significant hepatic iron overload. Patients and methods: Biochemical iron parameters and HFE mutation analysis (for the C282Y, H63D, and S65C mutations) were analysed in 250 healthy control subjects and collected retrospectively in 296 patients with suspected iron overload (elevated serum ferritin and/or transferrin saturation). The frequency of patients having at least mild iron overload, and mean serum ferritin and transferrin saturation values were calculated for each HFE genotype. For patients carrying the S65C mutation, clinical data, liver biopsy results, and amount of blood removed at phlebotomy were determined. Results: The HFE S65C mutation was found in 14 patients and eight controls. In controls, the S65C allele frequency was 1.6%. The S65C allele frequency was enriched in non-C282Y non-H63D chromosomes from patients (4.9%) compared with controls (1.9%) (p<0.05). Serum ferritin was significantly increased in controls carrying the S65C mutation compared with those without HFE mutations. Fifty per cent of controls and relatives having the S65C mutation had elevated serum ferritin levels or transferrin saturation. The number of iron overloaded patients was significantly higher among those having HFE S65C compared with those without any HFE mutation. Half of patients carrying the S65C mutation (7/14) had evidence of mild or moderate hepatic iron overload but no signs of extensive fibrosis in liver biopsies. Screening of relatives revealed one S65C homozygote who had no signs of iron overload. Compound heterozygosity with S65C and C282Y or H63D did not significantly increase the risk of iron overload compared with S65C heterozygosity alone. Conclusions: The HFE S65C mutation may lead to mild to moderate hepatic iron overload but neither clinically manifest haemochromatosis nor iron associated extensive liver fibrosis was encountered in any of the patients carrying this mutation.